(untitled) (Revista de História da UEG (REVHIST), 2022)
In this article, we analyze important points of the demonological theories of the Spanish Dominican Francisco de Vitoria (1486-1546), that help us understand the roots of Iberian skepticism about magic and witchcraft, based on faith in the Catholic insignia given by Providence to humanity as a remedy for the evil in the world. In addition, we sought to reinsert him in the list of important humanist writers who dealt with this theme in Europe during the same period. We study his Relectio Sobre a Magic (1539-1540), given in 1540 at the University of Salamanca, to understand his perspective on magic and witchcraft from the heterodox practices of the magical arts. Keywords: Magic. Demonology. Iberian Peninsula.